Evaluation of Dietary Choices, Preferences, Knowledge and Related Practices Among Pregnant Women Living in An Indian Setting - Ajantha (J Clin Diagn Res, 2015)
INTRODUCTION: Healthy and nutritious diet is very essential component of Antenatal care along with clinical advice. The objective of this study was to understand the dietary choices, preferences, knowledge and related practices among pregnant women living in an Indian setting. MATERIALS AND METHODS: Hundred pregnant women were enrolled in this cross-sectional study. Information about Socio-demographic profile, food item price and approach during inflation, nutrition related knowledge, attitude and practices and 24 hour dietary recall was acquired. RESULTS: Majority of the participants (87%) reported regular antenatal care visits and intake of iron and folic acid tablets. Eighty two percent of the participants were acquainted with standardized marks on food items and 64% of them reported checking of these marks before purchasing. Thirty two percent of the participants did not know about balanced diet. Fifty eight percent of the participants felled in fair category of dietary recall final scores. CONCLUSION: There is still vast room for improvement of the nutritional status of pregnant women as none of the participants were able to achieve excellent status on 24 hour food record scoring sheet.